Synthesis and Deprotection of 1,3-Dithianes and 1,3-Dithiolanes by Polyphosphoric Acid - Jin, Yong-Sheng; Zhang, Wei; Zhang, Da-Zhi; Qiao, Li-Ming; Wu, Qiu-Ye; Chen, Hai-Sheng (Asian Journal of Chemistry, 2010)
A simply, mild and efficient method for the deprotection of 1,3-dithianes and 1,3-dithiolanes to their corresponding carbonyl compounds using a mixture of polyphosphoric acid and acetic acid at 20-45 ºC is reported.